Effects of various logistics packaging on the quality and microbial variation of bigeye tuna (Thunnus obesus) - Cheng, Zhizhen; Pan, Weicong; Xian, Wendong; Yu, Jin; Weng, Xudong; Benjakul, Soottawat; Guidi, Alessandra; Ying, Xiaoguo; Deng, Shanggui (Frontiers in Nutrition, 2022)
Bigeye tuna (Thunnus obesus) is an economically valuable ocean fish species. It is susceptible to contamination during storage and transportation. Having proper transportation packaging and stable temperature during transportation are critical to prevent quality deterioration. However, the influence of packaging on retaining freshness in transit remains unknown. Here, the impact of different transportation packaging on the quality and microbiological variation of bigeye tuna during the logistics process was investigated by measuring physical-chemical indexes and microbial diversity. It turned out that aluminum foil paper (AFP) group had minimum temperature fluctuation, exhibited preferable water retaining capacity and color protection effect. AFP packaging could efficiently prevent TVB-N increase and microbial growth. After 40 h, the TVB-N value was 21.28 mg/100 g and microbial total plate count was 3.53 lg CFU/g, which was within the acceptable range. Temperature fluctuations and packaging materials had a major effect on the microbial community structure of bigeye tuna. Chitinophagaceae, Acinetobacter, and Knoellia were dominant in the AFP group, while Pseudomonas, Acinetobacter, and Macrococcus were dominant in the expanded polystyrene foam (EPSF) and European logistics (EUL) groups. AFP packaging could effectively slow down the growth and reproduction of Pseudomonas, restraining the growth of microorganisms and preserve the quality of bigeye tuna. This study provides insights into understanding the effects of packaging material on maintaining quality during logistics transportation.